The Golden Rule and the Economic Cycles - Honjo, Keiko (IMF Working Papers; Working Paper ;, 2007)
The present formulation of the golden rule in the United Kingdom allows fiscal performance to be tested explicitly on an ex-post basis. However, it requires precise dating of the economic cycle, which can lead to significant controversy. Also, the need to aim for current balance or better "over the cycle" may force fiscal policy to be procyclical toward the end of cycles. Using dynamic stochastic simulations, the paper suggests that making the formulation of the golden rule forward-looking and independent of the dating of the economic cycle would reduce the risk of procyclicality and enhance macroeconomic stability.